EDUKASI DAN DEMONSTRASI MPASI UNTUK MENINGKATKAN PEMAHAMAN KADER POSYANDU DAN IBU BALITA GUNA OPTIMALISASI GIZI ANAK DI DESA PESAWAHAN PROBOLINGGO - Rizky Budi; Akmal Nur Rafi; Putri Erlinda; Valda Isabella Pavytha; Sinta Nailul Latifah; Muchammad Saifuddin (As-Sidanah, 2024)
Stunting is a serious health issue that impacts children's long-term physical and cognitive development. Children affected by stunting face a higher risk of growth and development delays, potentially reducing their future quality of life. One method to prevent stunting is by providing appropriate complementary feeding (MP-ASI) that meets children's nutritional needs. The purpose this MP-ASI education and demonstration program to improve the knowledge and skills of Posyandu cadres and mothers of toddlers in Pesawahan Village, Probolinggo, in preparing and providing nutritionally balanced and age-appropriate MP-ASI. The program employed the ABCD (Assets Based Community Development) approach, designed to promote self-sufficiency and sustainable knowledge within the community by leveraging local resources. A total of 25 participants joined the program, which included educational sessions, interactive discussions, and hands-on practice in MP-ASI preparation. Evaluation was conducted using pre-test and post-test assessments, analyzed with IBM SPSS Statistics 16. The results of the hypothesis test showed a significant improvement in participants' understanding, with the average pre-test score rising from 78.00 to 90.00 in the post-test. Statistical analysis revealed a T-count of 6.928, exceeding the T-table value of 2.069, indicating that the MP-ASI education program effectively enhanced participants' knowledge and skills. In conclusion, this program successfully increased the knowledge and abilities of Posyandu cadres and mothers in relation to MP-ASI, contributing to optimizing children's nutrition and preventing stunting in Pesawahan Village.